2022
DOI: 10.1093/pm/pnac077
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pain Neuroscience Education in Patients with Fibromyalgia: A Systematic Review and Meta-Analysis

Abstract: Purpose To assess the effects of pain neuroscience education (PNE) on patients with fibromyalgia (FM) in terms of pain intensity, fibromyalgia impact, anxiety, and pain catastrophizing. Methods A systematic review and meta-analysis of randomized controlled trials was conducted. Standardized mean differences (SMDs) and 95% confidence intervals (CIs) were calculated with RStudio software for relevant outcomes and were pooled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
3
17
0
3
Order By: Relevance
“…Por otro lado, las intervenciones dirigidas a mejorar la monitorización del dolor y optimizar el manejo analgésico en un grupo de pacientes con dolor crónico de diferentes características, mostraron la reducción de los síntomas depresivos, el catastrofismo y la ansiedad como predictores de la reducción en la intensidad del dolor y la discapacidad relacionada con el dolor en el seguimiento (Scott et al, 2016). Estrategias basadas en la educación terapéutica han demostrado ser eficaces en la reducción de la intensidad del dolor y mejora de la discapacidad en dolor lumbar crónico y fibromialgia, pudiendo ser útiles en futuras aplicaciones para pacientes de artrosis de cadera y rodilla (Pires et al, 2015;Suso-Martí et al, 2022). Sin embargo, no parece que esta reducción en el dolor venga acompañada de una reducción en el catastrofismo en los estudios en pacientes de fibromialgia (Suso-Martí et al, 2022).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por otro lado, las intervenciones dirigidas a mejorar la monitorización del dolor y optimizar el manejo analgésico en un grupo de pacientes con dolor crónico de diferentes características, mostraron la reducción de los síntomas depresivos, el catastrofismo y la ansiedad como predictores de la reducción en la intensidad del dolor y la discapacidad relacionada con el dolor en el seguimiento (Scott et al, 2016). Estrategias basadas en la educación terapéutica han demostrado ser eficaces en la reducción de la intensidad del dolor y mejora de la discapacidad en dolor lumbar crónico y fibromialgia, pudiendo ser útiles en futuras aplicaciones para pacientes de artrosis de cadera y rodilla (Pires et al, 2015;Suso-Martí et al, 2022). Sin embargo, no parece que esta reducción en el dolor venga acompañada de una reducción en el catastrofismo en los estudios en pacientes de fibromialgia (Suso-Martí et al, 2022).…”
Section: Discussionunclassified
“…Estrategias basadas en la educación terapéutica han demostrado ser eficaces en la reducción de la intensidad del dolor y mejora de la discapacidad en dolor lumbar crónico y fibromialgia, pudiendo ser útiles en futuras aplicaciones para pacientes de artrosis de cadera y rodilla (Pires et al, 2015;Suso-Martí et al, 2022). Sin embargo, no parece que esta reducción en el dolor venga acompañada de una reducción en el catastrofismo en los estudios en pacientes de fibromialgia (Suso-Martí et al, 2022). Es posible que los efectos en el dolor se deban a la modificación de otras variables que deban ser analizadas en futuros estudios sobre educación terapéutica.…”
Section: Discussionunclassified
“…The SR/MA by Suso-Martí et al extracted the follow-up results from 8 RCTs and discovered a noteworthy phenomenon. 3 Although the patients with fibromyalgia showed a short-term improvement on some aspects of the Fibromyalgia Impact Questionnaire, some of the results manifest no improvement after a follow-up assessment a few months later. In other words, PNE might benefit fibromyalgia patients in the short term, but not in the long term.…”
mentioning
confidence: 90%
“…First, the authors selected only 4 studies in their SR/MA, which they admitted as a limitation; nevertheless, we found an SR/MA with a similar topic which includes 8 studies. 3 After comparing the searching strategies, Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagrams, and the selected RCTs of the 2 SR/ MAs, we consider that the authors of the former SR/MA excluded some RCTs not because their selection was rather strict, but because their searching strategy did not include enough synonyms for fibromyalgia and PNE. For example, 2 RCTs selected in the latter SR/MA titled "How Much Is Needed?…”
mentioning
confidence: 99%
“…First, our study 2 aimed to evaluate whether adding PNE to a multimodal approach has additional benefits in patients with FM. The SR/MA 3 differs from our study 2 in terms of the aim and eligibility criteria, intervention and comparison criteria. For example, the intervention methods used in our study 2 were defined as multimodal.…”
mentioning
confidence: 94%